Interconnecting violences for research, policy and activism: concluding reflections - Hearn, Jeff (Interconnecting the violences of men, 2025)
This final chapter presents some concluding reflections on the book as a whole and the main themes that are addressed in the contributions: first, violences in the plural; second, men, masculinities, men’s violences and violent masculinities; and third, their intersectional gendered relations and interconnections. In particular, three cross-cutting issues are discussed: the kinds of violences examined by our contributors; the main interconnections stressed by them in their analyses; the nature of these interconnections recognised; and before comments and suggestions for future work for research, policy and activism.